Conscious and Unconscious Thought in Risky Choice: Testing the Capacity Principle and the Appropriate Weighting Principle of Unconscious Thought Theory - Ashby, Nathaniel J.; Glöckner, Andreas; Dickert, Stephan (Frontiers in Psychology, 2011)
Daily we make decisions ranging from the mundane to the seemingly pivotal that shape our lives. Assuming rationality, all relevant information about one’s options should be thoroughly examined in order to make the best choice. However, some findings suggest that under specific circumstances thinking too much has disadvantageous effects on decision quality and that it might be best to let the unconscious do the busy work. In three studies we test the capacity assumption and the appropriate weighting principle of unconscious thought theory using a classic risky choice paradigm and including a ‘deliberation with information’ condition. Although we replicate an advantage for unconscious thought over ‘deliberation without information’, we find that ‘deliberation with information’ equals or outperforms unconscious thought in risky choices. These results speak against the generality of the assumption that unconscious thought has a higher capacity for information integration and show that this capacity assumption does not hold in all domains. We furthermore show that ‘deliberate thought with information’ leads to more differentiated knowledge compared to unconscious thought which speaks against the generality of the appropriate weighting assumption.